Infliximab Salvage Therapy after Cyclosporine in an Acute Flare of Chronic Ulcerative Colitis. (1st May 2003) - Lam, ECS; Bailey, RJ
Abstract : Although infliximab (Remicade, Schering Canada Inc, Quebec) therapy has been well studied in steroid refractory Crohn's disease, its use remains controversial in chronic ulcerative colitis. A 24-year-old woman with a 14-year history of well controlled left sided ulcerative colitis presented with an acute flare. Clinical, endoscopic and biopsy evidence of an acute flare of ulcerative pancolitis were present. There was no response to intravenous steroids but improvement was seen after receiving 14 days of intravenous cyclosporine (4 mg/kg/day continuous infusion). The patient was discharged from hospital with azathioprine (2.5 mg/kg/day) and low dose oral cyclosporine (4 mg/kg/day). She presented with worsening symptoms seven days after discharge. Because of the patient's unwillingness for surgery, she instead received two injections of infliximab 5 mg/kg at week 0 and week 2. An initial response occurred, but her clinical improvement was not durable. Colectomy was performed four weeks later. This is the first report of infliximab as a salvage therapy in an acute flare of chronic ulcerative colitis following failure of cyclosporine.